Handbook of adhesion - Packham, D. E. (David Ernest), 1939- (John Wiley, 2005)
This Second Edition provides concise and authoritative articles covering many aspects of the science and technology associated with adhesion and adhesives. The articles are structured in such a way, with internal cross-referencing and external literature references, that the reader can build up a broader and deeper understanding, as their needs require. This book includes many new articles covering developments which have risen in prominence in the intervening years, such as scanning probe techniques, the surface forces apparatus and the relation between adhesion and fractal surfaces. The scope of the Handbook, which features nearly 250 articles from over 60 authors, includes the background science (physics, chemistry and material science), engineering, and aspects of adhesion relevant to the use of adhesives. This book is intended for scientists and engineers in both academia and industry, requiring an understanding of the various facets of adhesion. --